ANALISIS STRATEGI PEMASARAN DENGAN METODE SWOT ANALYSIS DAN MARKETING MIX - Anwa (PPPM POLTESA, 2022)
Fresh Cow Milk UKM Wijaya is one of the SMEs which is engaged in cattle farming as well as running UHT milk processing. One of the problems faced by Wijaya's Fresh Cows Milk UKM is the inadequate marketing activities, because the Wijaya Fresh Cow Milk UKM has various limitations, including business capital, market information, and supporting technology. This study aims to determine the marketing mix, internal and external influencing factors of SMEs, and the formulation of alternative marketing strategies using the IFE / EFE matrix method and the SWOT matrix. The results of this study are the internal strength factors that have the most influence is having as many as 15 dairy cows, and product prices that are affordable by school children and the general public, a score of 0.45. The most influential internal factor of weakness does not have adequate technology, a score of 0.3. The external factor, the most influential opportunity, is that there are no competitors who can produce pure cow's milk in the city area, with a score of 0.65. The most influential external threat factor is rupiah exchange rate inflation, a score of 0.42. The total IFE score is 2.59 and EFE 2.48, the strategy with IE matrix is market penetration and product development. The proposed strategy with a SWOT matrix based on the IE strategy is to improve product quality to retain old consumers and to attract new customers (S-O and W-T Strategies), and to make improvements to products by adding flavors and adding important information to product packaging.